Influence of Technology on Teaching Learning Approaches and Modalities among Elementary School Teachers - Obaña, Phoebe Jehn; Espartero, Helen (JPAIR Multidisciplinary Research, 2025)
In the current global scenario, the internet is increasingly becoming a central informational medium, transforming how people learn, teach, and communicate. There is inadequacy in providing ICT facilities to schools, which hinders the use of ICT inside the classroom to enrich the teaching-learning process and modalities. This research used descriptive and correlational research designs to determine the influence of technology on teaching-learning approaches and modalities. The researcher used simple random sampling by using Slovin's Formula. The study was conducted in the elementary schools of the Division of Tacurong, Philippines. The mean, standard deviation, and Pearson Product Moment correlation were utilized, the hypothesis was tested, and result was less than .05. The study revealed that Technology exerts a very high influence on education, particularly through digital devices, software applications, and ICT. Teaching-learning approaches are effectively implemented to a full extent, as reflected in the strong agreement among respondents. Educational institutions employ multiple teaching-learning modalities to a high extent, with face-to-face learning remaining the most preferred. These results emphasize the need for continued investment in educational technology to foster more dynamic and effective learning environments and highlight the importance of integrating ICT-driven strategies to support distance learning while also enhancing the role of digital tools in traditional and blended settings.
Keywords: Education; technology; modalities; teaching-learning approaches; influence; ICT; descriptive; correlational research design; Philippines